A Cross-sectional study to assess knowledge, practice and self- reported morbidity symptoms of pesticide use among farm women - Medithi, Srujana; Kasa, Yogeswar D; Lari, Summaiya; Nagaraju, Raju; Kodali, Venkaiah; Jonnalagadda, Padmaja R (Indian Journal of Community Health, 2017)
Background: Inevitable pesticide use in Indian agriculture has posed an increased risk of exposure to the farmers, which may lead to adverse health manifestations. Therefore, it is essential that the farmers must be aware of the harmful effects of pesticides. Aims and Objectives: To assess knowledge, practice and identify self-reported morbidity symptoms associated with pesticide use among farm women in the identified villages of Telangana, India. Materials and Methods: Community based cross-sectional study was conducted using a pre-tested questionnaire to carry out the survey among farmwomen. Results: 129 women working in agricultural farms were included in the study. Meagre knowledge regarding route of pesticide exposure was observed. Majority of them were not aware of toxicity symbols and never read the precautions on the pesticide containers. Inaccessibility was the main reason for insubstantial use of personal protective equipments (PPEs). Unsafe storage and disposal practices of containers were observed. Weakness (57.3%), headache (52%) and itching of skin (51.1%) were the common morbidity symptoms. Significant association was found between morbidity symptoms and use of PPE and hygienic practices, indicating importance of such practices. Conclusion: Improving knowledge which influences their practices and encouraging PPE use might be useful to remediate these issues. Monitoring studies may further aid to obtain the outcome of the awareness programmes and subsequently improved intervention methods can also be implemented.